Implementation of Human Resources Planning for Crowdfunding Platform Company at PT. Esa Dana Unggul - Irfan Irfan; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Dimas Angga Negoro (Cakrawala Repositori IMWI, 2023)
PT Esa Dana Unggul (EsaDana) is a company that meets the needs and wants of every consumer in investment needs through the Securities Crowd Funding platform. Analysis of products and services offered to consumers is the Esa Dana Platform as a crowdfunding platform that brings together investors and companies that need financing in a cheap and easy way to invest and minimize the risk of loss. Esa Dana's human capital planning refers to the knowledge, skills and competencies possessed by individuals in the organization. By conducting proper planning to manage and develop human capital, companies ensure that they have a competent, committed and highly competitive team. Through human capital planning strategies, companies can maximize employee potential, increase productivity, and respond more effectively to market changes. In carrying out the strategy, Human Resources Planning at EsaDana Company will focus on the Market Penetration Strategy in the form of optimizing online channels. This strategy was taken as a solution in introducing the brand and product as well as running a new company engaged in crowdfunding services in Indonesia. PT Esa Dana Unggul (EsaDana) implements Human Resources strategies in accordance with applicable regulations in Indonesia, such as payroll systems, employee welfare, pensions, health insurance, overtime pay, and holiday allowances. In the first year, Esa Dana will employ as many as .... employees.